2007
DOI: 10.1126/science.1138684
|View full text |Cite
|
Sign up to set email alerts
|

Positive Regulation of Itk PH Domain Function by Soluble IP 4

Abstract: Pleckstrin homology (PH) domain-mediated protein recruitment to cellular membranes is of paramount importance for signal transduction. The recruitment of many PH domains is controlled through production and turnover of their membrane ligand, phosphatidylinositol 3,4,5-trisphosphate (PIP3). We show that phosphorylation of the second messenger inositol 1,4,5-trisphosphate (IP3) into inositol 1,3,4,5-tetrakisphosphate (IP4) establishes another mode of PH domain regulation through a soluble ligand. At physiologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
228
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 98 publications
(239 citation statements)
references
References 17 publications
10
228
1
Order By: Relevance
“…Yes. Recent studies of several IPKs have demonstrated their essential involvement in organism development and function (17,(36)(37)(38)(39)(40)(41). Given the highly orchestrated nature of these processes, it is reasonable to conclude that the production of an IP code that emerges from IP 3 is involved in the execution of these instructions.…”
Section: G Protein Activation Along With Expression Of the Four Evolmentioning
confidence: 99%
See 1 more Smart Citation
“…Yes. Recent studies of several IPKs have demonstrated their essential involvement in organism development and function (17,(36)(37)(38)(39)(40)(41). Given the highly orchestrated nature of these processes, it is reasonable to conclude that the production of an IP code that emerges from IP 3 is involved in the execution of these instructions.…”
Section: G Protein Activation Along With Expression Of the Four Evolmentioning
confidence: 99%
“…This notion is further supported by our current studies in mammalian cells. Additionally, data from both uni-and multicellular organisms have provided clues into the intracellular receptors that participate in decoding the IPK-dependent IP 4 , IP 5 , IP 6 , and PP-IP messengers, in particular with respect to mRNA export (49,50), chromatin remodeling (46,47), RNA editing (53), protein phosphorylation (54), phosphate signaling (25,51), auxin biology (41), and immune function (40). Collectively, these data provide exciting evidence supporting a role for an IPKdependent IP code in signal-transduction pathways.…”
Section: G Protein Activation Along With Expression Of the Four Evolmentioning
confidence: 99%
“…Ins (1,3,4,5)P4, the product of InsP3KB, can exerts its function via binding to other cellular targets. Several proteins, including GAP1 IP4BP (also known as Rasa3), α-centaurin, and GAP1 m , also specifically interact with Ins(1,3,4,5)P4, 18,19 suggesting that the functions of these proteins might also be regulated by Ins (1,3,4,5) 21 Whether a similar mechanism also exists in hematopoietic progenitors was not investigated. InsP3K has also been reported to be a potential modulator of calcium mobilization, since it can decrease the level of Ins(1,4,5)P3, which mediates calcium release from internal store, by converting it to Ins(1,3,4,5)P4.…”
Section: Ins(1345)p4 and Insp3kb Regulate Innate Immunity Via Modumentioning
confidence: 99%
“…As PIP 3 can be generated via stimulation of many different receptors, including immunoreceptors, G protein-coupled receptors, as well as membrane-spanning tyrosine kinases, PI3K-induced activation of TFKs can be achieved through multiple pathways. At physiological concentrations, IP 4 enhances the binding of Itk's PH domain to PIP 3 (Huang et al, 2007). In the case of Btk, its selective interaction with particular phosphoinositides has been addressed using biochemical and cell-biological methods (Hamman et al, 2002;Nore et al, 2000;Rameh et al, 1997;Saito et al, 2001;Salim et al, 1996;Varnai et al, 2005) as well as structure determination (Baraldi et al, 1999).…”
Section: B Regulation Of Ph Domain Binding By Phosphoinositide 3-kinmentioning
confidence: 99%
“…PIP 3 is the most negatively charged plasma membrane lipid, concentration of which can increase 40-fold within seconds after PI3K activation (Stephens et al, 1993). PIP 3 binding characterizes the PH domain of Btk (Manna et al, 2007;Nore et al, 2000;Rameh et al, 1997;Salim et al, 1996;Watanabe et al, 2003), Bmx (Ekman et al, 2000;Jiang et al, 2007;Qiu et al, 1998), Itk (August et al, 1997;Huang et al, 2007;Lu et al, 1998), as well as Tec (Kane and Watkins, 2005;Lachance et al, 2002;Tomlinson et al, 2004). TFKs have widely varying binding specificities and affinities for inositol compounds (Kojima et al, 1997).…”
Section: B Regulation Of Ph Domain Binding By Phosphoinositide 3-kinmentioning
confidence: 99%